A preocupação com a água nos livros de Gênesis e Êxodo - Ramos, Marivan Soares (2025)
In the last two decades, there have been significant thematic advances in the reading and interpretation of biblical texts, read as the Word of God by the Judeo-Christian community and accepted as cultural heritage by humanity. Until then, research that was more exclusively interested in reflections on God and/or the human being in these millennia-old literary traditions prevailed. As a result, when reading the Bible, there was also the danger of favouring either theocentrism or anthropocentrism. Today, however, there is greater awareness that this ancient religious literature also looks at non-human beings: air, water, soil, temperature, plants and animals. Environmental dimensions are therefore added to reflections on God and the human being. With this thematic discovery, however, came the task of rereading the most diverse biblical writings with this new hermeneutical key and/or environmental issue in mind. This is the challenge taken up in this Doctoral Thesis: to offer a valid contribution to the field in which the socio-environmental dimensions present in the Bible are studied. In order not to lose immediate contact with the biblical texts that make up this literary-religious artwork, we aimed for the narrower question of how the books of Genesis and Exodus concern themselves with water, one of the four abiotic beings, indispensable for the survival of plants, animals and human beings in this world. To put it more broadly, it is possible to say that the ninety chapters that make up the books of Genesis and Exodus, in their narratives and even in their legal formulations, repeatedly give centrality and importance to water. In other words, in the first two books of the Pentateuch, and thus in the first two writings of any Judeo-Christian Bible, water becomes a theological issue, leading the listener-reader to think about God and all beings created by Him, human and non-human. With this, prevails the imperative to respect water as a divine word